La position de l’énoncé rapportant au discours direct : entre dire et faire - Aurélie CECCALDI-HAMET (E-REA)
Reporting clauses of direct speech – especially in final and medial positions – are typical of literary fiction. Their study goes well beyond the limits of form, the exploration of which opens the way for interpretation. Literary texts have a pragmatic structure which is the complex “relationship among all the language users of the text” (Adams) and the type of reported speech as well as the type of reporting clause can be considered as choices with syntactic and stylistic implications throughout the literary works.